2015
DOI: 10.3109/10929088.2015.1076047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coordinate-system construction methods on postoperative computed tomography evaluation of implant orientation after total hip arthroplasty

Abstract: Objective: In total hip arthroplasty, it is important to assess postoperative implant orientation. The computed tomography-based (CT-based) three-dimensional (3D) templating method using 3D preoperative planning software is generally recommended. In this method, postoperative implant orientation within a bony coordinate system can be measured by overlaying a 3D computerized model of the implant on a real postoperative CT image of the implant. The bony coordinate system consists of several reference points (RPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In addition, 3D planning entails an additional annual cost to hospitals, and Huppertz et al reported an estimated direct cost of 3D preoperative THA planning of EUR 53–116 per patient [ 37 ], but the total cost of THA may be reduced by up to 25.7% through automatic selection of hip implants [ 17 , 38 ]. This requires the availability of managerial support, technical engineers, and medical personnel to enhance the learning curve and compensate for barriers to adoption [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 3D planning entails an additional annual cost to hospitals, and Huppertz et al reported an estimated direct cost of 3D preoperative THA planning of EUR 53–116 per patient [ 37 ], but the total cost of THA may be reduced by up to 25.7% through automatic selection of hip implants [ 17 , 38 ]. This requires the availability of managerial support, technical engineers, and medical personnel to enhance the learning curve and compensate for barriers to adoption [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate their system, the authors aligned pre- and postoperative CT scans through image registration using normalised mutual information (NMI) as metric. Kyo et al [ 43 ] evaluated implant orientation in postoperative CT images after total hip arthroplasty, by overlaying a 3D model of the implant on a postoperative CT image of the implant. In 2022, Gubian et al [ 44 ] evaluated CT-navigated pedicle screw placement, by comparing the preoperative trajectory plan with the corresponding postoperative screw position, determined by manual segmentation of the postoperative CT. Uozumi et al [ 45 ] proposed an automatic 3D evaluation of screw placement after anterior cruciate ligament reconstruction using multidetector CT images.…”
Section: Introductionmentioning
confidence: 99%